Efficacy of different medications in the treatment of gynaecological tumours: a clinical meta-analysis - Chen, Qiaoying (Frontiers in Oncology, 2024)
A gynaecological tumour is one of the world's leading causes of death for women globally. Among women, cancer is the 8th most common cause of death. Since there are no such programmes, the majority of women who are diagnosed with the condition are either in advanced stages or do not respond well to current treatments. Even if patients react to the treatments, they still risk having the cancer return, at which point any further medical intervention is met with resistance.Method: For this study, we selected the systemic reviews and articles that have the use of different medications used for the treatment of gynaecological tumours.Regarding metformin use, this study found a positive relationship between higher survival and metformin use. Five of the studies that examined the use of statins revealed a link between statin use and higher overall and/or progression-free survival rates. Individuals on lipophilic and hydrophilic statins would do better. Research evaluating beta-blocker use during neoadjuvant treatment revealed a timevarying effect, with improved survival seen across all users early in the follow-up period. However, only non-selective beta-blocker users demonstrated a correlation with higher survival after five years. One study found that the benefits of aspirin use were significant, but the advantage for continuous users (both before and after diagnosis) was minimal.Conclusions on the association between gynaecological tumour survival and NA-NSAIDs, metformin, beta-blockers, and aspirin cannot be drawn due to insufficient evidence. However, the vast majority of statin studies have demonstrated that users had higher rates of survival. Bias, however, bias may affect the results of the studies.